Reformulating Indonesia’s Consumer Protection Law in the AI-Driven Digital Economy: A Gap Analysis and Regulatory Roadmap - Poernomo, Sri Lestari; Husen, La Ode; Sivakumar, S.; Aulia, Nur Afti; Muzakkir, Abd. Kahar (Khazanah Hukum, 2026)
The exponential growth of the AI-driven digital economy in Indonesia has triggered a systemic regulatory failure, evidenced by a 275% surge in consumer disputes due to the inability of positive law to address algorithmic risks. This research aims to reformulate Indonesia’s consumer protection legal architecture to resolve the structural obsolescence of Law Number 8 of 1999 and sectoral regulatory fragmentation. Employing a normative-juridical method integrated with a comparative analysis of the EU Digital Services Act and the EU AI Act, this study diagnoses the inadequacy of the fault-based liability regime in addressing algorithmic opacity. The findings indicate that consumer protection against systemic risks demands a paradigm shift from ex post redress to ex ante risk governance. As a concrete solution, this study constructs an adaptive legal model grounded in the Precautionary Principle, encompassing four main regulatory pillars: mandatory AIA, platform observability, tiered liability with presumption of causality, and digital rights codification. The primary originality of this research lies in the formulation of an implementation roadmap based on the Triple Helix model, which operationalizes these norms through concrete collaborative stages, ranging from establishing a regulatory sandbox to founding an independent digital supervisory authority. These policy implications provide a strategic blueprint for policymakers to transform the legal system into the foundation of a fair, trustworthy, and sustainable digital ecosystem.